Community-Based Rehabilitation in Bangladesh, Health Components Need to be Integrated with Primary Health Care - Rahman, Md Shahidur (Journal of Enam Medical College, 2018)
Community-based rehabilitation (CBR) is defined as a strategy within general community development for the rehabilitation, equalization of opportunities, poverty reduction and social inclusion of people with disabilities. The role of CBR is to work closely with the health sector to ensure that the needs of people with disabilities and their family members are addressed in the areas of health promotion, prevention, medical care, rehabilitation and assistive devices. CBR also needs to work with individuals and their families to facilitate their access to health services and to work with other sectors to ensure that all aspects of health are addressed. Health components of CBR as per WHO guidelines are grossly neglected in Bangladesh. Some government and non-government organizations are working independently, but health components are inadequately addressed. We observed that primary health care, if integrated with medical rehabilitation of disabled, will better address the need and help bring disabled into mainstream of development. Health care providers at grass root level need to be trained in CBR activities which can be arranged centrally with health ministry, social welfare ministry and rehabilitation specialists. In this review we have tried to reveal the health components of CBR in global and Bangladesh context and importance of integrating health components of CBR with primary health care. J Enam Med Col 2018; 8(1): 41-45